OPTIMIZATION OF ENERGY EFFICIENCY PERFORMANCE AND SPACE COMFORT IN COWORKING SPACE BUILDING, CASE STUDY: RELATIONSHIP OF COWORKING SPACE AND CAFE - Agustina Tri Mulyani; Christian Nindyaputra Octarino (Universitas Indraprasta PGRI, 2023)
After the COVID-19 pandemic, people began to embrace flexible working and coworking space became one of the comfortable work spaces. The culture of